Point of care detection of SARS-CoV-2 antibodies and neutralisation capacity—lateral flow immunoassay evaluation compared to commercial assay to inform potential role in therapeutic and surveillance practices - McGrath, Jonathan; O'Doherty, Laura; Conlon, Niall; Dunne, Jean; Brady, Gareth; Ibrahim, Aya; McCormack, William; Walsh, Cathal; Domegan, Lisa; Walsh, Shane; Kenny, Claire; Allen, Niamh; et al. (Frontiers in Public Health, 2023)
Introduction As the COVID-19 pandemic moves towards endemic status, testing strategies are being de-escalated. Rapid and effective point of care test (POCT) assessment of SARS-CoV-2 immune response can inform clinical decision-making and epidemiological monitoring of disease. This cross-sectional seroprevalence study of anti-SARS-CoV-2 antibodies in Irish healthcare workers assessed how rapid anti-SARS-CoV-2 antibody testing can be compared to a standard laboratory assay, discusses its effectiveness in neutralisation assessment and its uses into the future of the pandemic. Methods A point of care lateral flow immunoassay (LFA) detecting anti-SARS-CoV-2 spike (S)-receptor binding domain (RBD) neutralising antibodies (Healgen SARS-CoV-2 Neutralizing Antibody Rapid Test Cassette) was compared to the Roche Elecsys/-S anti-SARS-CoV-2 antibody assays and an in vitro surrogate neutralisation assay. Correlation between anti-spike (S), anti-nucleocapsid (N) titres and in vitro neutralisation was also assessed. Results 1,777 serology samples were tested using the Roche Elecsys/-S anti-SARS-CoV-2 assays to detect total anti-N/S antibodies. 1,562 samples were tested using the POC LFA (including 50 negative controls) and 90 tested using an in vitro ACE2-RBD binding inhibition surrogate neutralisation assay. The POCT demonstrated 97.7% sensitivity, 100% specificity, a Positive Predictive Value (PPV) of 100% and a Negative Predictive Value (NPV) of 61% in comparison to the commercial assay. Anti-S antibody titres determined by the Roche assay stratified by the POC LFA result groups demonstrated statistically significant differences between the ‘Positive’ and ‘Negative’ LFA groups (p <0.0001) and the ‘Weak Positive’ and ‘Positive’ LFA groups (p <0.0001). No statistically significant difference in ACE2-RBD binding inhibition was demonstrated when stratified by the LFA POC results. A positive, statistically significant correlation was demonstrated between the in vitro pseudo-neutralisation assay results and anti-S antibody titres (rho 0.423, p <0.001) and anti-N antibody titres (rho= 0.55, p <0.0001). Conclusion High sensitivity, specificity and PPV was demonstrated for the POC LFA for the detection of anti S-RBD antibodies in comparison to the commercial assay. The LFA was not a reliable determinant of neutralisation capacity of identified antibodies. POC LFA are useful tools in sero-epidemiology settings, pandemic preparedness and may act as supportive tools in treatment decisions through the rapid identification of anti-Spike antibodies.